Regulatory arbitrage, credit expansion and the development of shadow banking in China- from the perspective of bank-issued wealth management products - Kang, Kuan; Mohd Ashhari, Zariyawati; Yahya, Mohamed Hisham; Wei Ni, Soh (Human Resource Management Academic Research Society, 2024)
Bank-issued Wealth Management Products (WMPs) are perceived as the largest part of China’s shadow banking system and has undergone dramatical growth during the past decade. This study uses a sample of 46 commercial banks and adopts two-step system GMM to investigate the determinants for the rise of WMPs from 2015 to 2021 in China. The results show that WMPs, as the essential deposit substitution and off-balance-sheet activities of commercial banks, are mainly driven by the motivation to satisfy credit expansion and circumvent regulatory requirements on liquidity and capital adequacy. The results demonstrate that regulatory arbitrage is the primary driving of shadow banking activities. Besides, this study further explores the heterogeneity between nationwide commercial banks (NCBs) and local commercial banks (LCBs) on the motivation to issue WMPs. Comparing with NCBs, LCBs tend to issue more WMPs to raise funds and relieve their supervisory pressure.